1976
DOI: 10.1128/aac.10.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interpretation of Cephradine Levels in Serum After Intravenous and Extravascular Administration in Humans

Abstract: Pharmacokinetic parameters were calculated from intravenous data based upon a two-compartment open model. These parameters were subsequently used to determine the absorption rates and bioavailability of cephradine administered intramuscularly and orally. The results indicate that cephradine obeys dose-independent kinetics and that biological availability is complete from all dosage forms.Cephradine, a semisynthetic cephalosporin derivative chemically designated as 7-[D-2-amino(1,4 -cyclohexadien -1 -yl)acetami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…in healthy chickens showed that, the disposition best fitted by a two compartments open model. The obtained result was consistent with that reported for cephradine in human (Rattie et al, 1976) and goats (El-Sayed et al 1994). In this study, the Vdss for cephradine was 321.53 mL/kg, suggesting a higher penetration through biological membranes and tissue after IV injection in broiler chickens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…in healthy chickens showed that, the disposition best fitted by a two compartments open model. The obtained result was consistent with that reported for cephradine in human (Rattie et al, 1976) and goats (El-Sayed et al 1994). In this study, the Vdss for cephradine was 321.53 mL/kg, suggesting a higher penetration through biological membranes and tissue after IV injection in broiler chickens.…”
Section: Discussionsupporting
confidence: 93%
“…Cephradine half-life is reported to range from 0.6 to 1.8 hours (Wise, 1990). The pharmacokinetics of cephradine were investigated in mice, rats, dogs (Weliky et al, 1974), human (Rattie et al, 1976;Roberts et al, 1981), foals (Henry et al, 1992), goats (El-Sayed et al, 1994) and chickens (El-Sayed et al, 2016). To our knowledge, only a few studies about disposition of cephardine in broilers are available.…”
Section: Introductionmentioning
confidence: 99%
“…Rattie et a l . (10) demonstrated that a linear relationship between dose (0.25-1.0 g) and both peak concentration and AUC exists for cephradine. Pfeffer et al (9) reported that a linear relationship in peak concentration and AUC exists for cephalexin a t doses of 0.25 and 0.5 g. The reported pharmacokinetic parameters from these studies are similar to the present findings; therefore, dose-dependent kinetics do not appear to exist with these drugs.…”
Section: Resultsmentioning
confidence: 97%
“…Food in the gastrointestinal tract may delay the absorption of cefradine, but the total amount of absorption will not be affected. PK parameters of oral cefradine capsules reported in prior research [13][14][15][16][17][18][19] were remarkably similar, and the concentrations of different doses of cefradine capsules approached the peak about 1 hour after fasting oral administration. The data from the current study showed that peak time was reached about 2.5 hours after administration, and the half-life was about 1 hour.…”
Section: Discussionmentioning
confidence: 71%
“…Rattie et al 13 showed the results from a doublecrossover study of 20 volunteers treated with oral 250or 500-mg cefradine capsules and 22 volunteers treated with 1000-mg cefradine capsules, the PK characteristics of the 250-and 1000-mg cefradine capsules were linearly correlated. A bioequivalence study 11 of 500mg cefradine capsules orally administered under the fasting conditions for 24 healthy volunteers in Korea also showed the similar results compared with the reference preparation, as the test and reference preparations were found to be bioequivalent.…”
Section: Discussionmentioning
confidence: 99%